KEADAAN ELEMEN JALAN HUTAN DAN POTENSINYA DALAM MEMPERCEPAT EROSI TANAH - Djaban Tinambunan (Jurnal Penelitian Hasil Hutan, 1989)
A  study  on  the  forest  road  element   conditions   in relation  to soil  erosion  potentials   was carried out  at two  logging companies   in Buntok   area,   Central  Kalimantan   in  1988.  Road   elements   measured   in  the  field  are those  related  to  the Universal Soil  Loss  Equation   factors  such  as road openings,  surfaces,  slopes,  ditches,  culverts,  cuts,  fills, diversion  ditches, and the incidence  of  vegetation.The  results  showed   that  forest   road  elements   are in  the  condition   of  high potentials   for  accelerating  soil  erosion.Factors  that  caused  this problem,   as identified   in the field,  are:  long and steep  slopes,  wide ground  openings,  and  bare soil surfaces,  in addition   to  the  originally  sensitive  to  erosion  soil  type,  and  hot  and  wet  weather.Qualitatively,   it is realized  that soil erosion  is quite  serious.  Therefore,  further  study  is necessary  in order  to find  the quantitative   amount   of  soil erosion  occured  in  the  area.